C-reactive protein mediates the association between leisure-time physical activity and lung function in middle-aged and older adults - Chen, Meng (BMC Public Health, 2020)
BACKGROUND: Although previous studies have reported the benefits of physical activity (PA) to lung function in middle-aged and older adults, the biological mechanisms are still unclear. This study aimed to assess the extent to which C-reactive protein (CRP) mediates the association between leisure-time PA and lung function. METHODS: A population-based sample was recruited from English Longitudinal Study of Ageing (ELSA), Wave 6 (2012–2013). PA was self-reported by questionnaires. CRP was analyzed from peripheral blood. Lung function parameters including forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) were measured by using a spirometer. Baron and Kenny’s causal steps method and multiple linear regression models based on the Karlson/Holm/Bree (KHB) method were used to assess the mediating effect. RESULTS: Among 6875 participants, 28.4% were classified into low PA, 49.8% into moderate PA, and 21.8% into high PA. Multiple linear regression models suggested that higher PA was associated with lower levels of CRP (β = − 0.048, P = 0.002 for moderate PA; β = − 0.108, P < 0.001 for high PA). CRP negatively correlated with FEV1 (β = − 0.180, P < 0.001) and FVC (β = − 0.181, P < 0.001). Higher levels of PA were associated with better FEV1 (β = 0.085, P < 0.001 for moderate PA; β = 0.150, P < 0.001 for high PA) and FVC (β = 0.131, P < 0.001 for moderate PA; β = 0.211, P < 0.001 for high PA). After introducing the CRP into the models, regression coefficients of PA with FEV1 (β = 0.077, P < 0.001 for moderated PA; β = 0.130, P < 0.001 for high PA) and FVC (β = 0.123, P < 0.001 for moderated PA; β = 0.188, P < 0.001 for high PA) decreased. The indirect effect of high PA on lung function via CRP was significant, with 9.42–12.99% of the total effect being mediated. CONCLUSIONS: The association between PA and lung function is mediated by CRP, suggesting that this association may be partially explained by an inflammation-related biological mechanism. This finding highlights the possible importance of PA in systemic inflammation and lung function, thus, middle-aged and older adults should be encouraged to enhance PA levels.